Polycystic Ovary Syndrome and Labor Market Attachment: Sequence Analysis - Beata Vivien Boldis; Beata Vivien Boldis; Ilona Grünberger; Jonas Helgertz; Jonas Helgertz; Agneta Cederström (International Journal of Public Health)
ObjectivesPolycystic ovary syndrome (PCOS) is an endocrine disorder in women of fertile age which may also affect the labor market attachment. We investigated labor market attachment trajectories among working age women diagnosed with PCOS.MethodsA cohort of 157,356 women born in 1975–1977 were followed annually between the ages of 30 and 39, using data from Swedish administrative registers. Multinomial logistic regression was employed to assess associations between being diagnosed with PCOS (after the age of 15) and belonging to the identified clusters of labor market attachment trajectories.ResultsWomen with PCOS spent less time in employment and were more dependent on sickness benefits during the follow-up time than those without PCOS. Five labor market attachment clusters were identified: stable employment, education into employment, labor market exclusion, continuously unstable position, long-term sickness. Compared to being in the stable employment cluster, women diagnosed with PCOS were more likely to experience long-term sickness [RRR (relative risk ratio): 1.97 (CI: 1.90–2.05)], and education into employment [RRR: 1.11 (CI: 1.07–1.15)].ConclusionPCOS can lead to disadvantaged labor market outcomes. Better strategies are needed to prevent economic exclusion among women diagnosed with PCOS.